4(x-8)-6x=-12

Simple and best practice solution for 4(x-8)-6x=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-8)-6x=-12 equation:


Simplifying
4(x + -8) + -6x = -12

Reorder the terms:
4(-8 + x) + -6x = -12
(-8 * 4 + x * 4) + -6x = -12
(-32 + 4x) + -6x = -12

Combine like terms: 4x + -6x = -2x
-32 + -2x = -12

Solving
-32 + -2x = -12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '32' to each side of the equation.
-32 + 32 + -2x = -12 + 32

Combine like terms: -32 + 32 = 0
0 + -2x = -12 + 32
-2x = -12 + 32

Combine like terms: -12 + 32 = 20
-2x = 20

Divide each side by '-2'.
x = -10

Simplifying
x = -10

See similar equations:

| z^7+5z^6=0 | | 5m+m=12 | | 7/x=2-3/x | | 1078/14 | | 3r^2=2+7r | | 22=d-2 | | 4y+8=4 | | -4(5n+4)=-16-n | | -9w-4=14 | | x^2+3x-1=7x+22 | | -3(2p+4)=-15-5p | | (8x^-3y^3z^6)^1/3 | | 2=(v-7)(v-1) | | 8x-(3x-10)=30 | | 3*-4+6-2x=-2 | | (1+w)(4w+2)=0 | | k-5/7=2 | | 14(3/7x) | | 4n+2(10-n)=3 | | -21+(-56)= | | 5x+2(x+4)=-6 | | -6(6x+7)=-150 | | -21+56= | | 5x+4-7x=5+x-23 | | 5v=v+36 | | 0.05+0.35= | | -2-b=8 | | 5(x-4)=70 | | 9x-(2x-6)=41 | | 2k-30=-2(6k+8) | | 21+(-56)= | | 5m-2-9m-3=7+m+23 |

Equations solver categories